2008
DOI: 10.1016/j.healthpol.2008.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Strategies that promote high quality care in Indonesia

Abstract: Objectives-To investigate factors predicting the quality of care received using a nationally representative dataset from Indonesia.Data Sources-The study combines two surveys in 13 provinces: a household survey of 2451 women who delivered a live birth in 1992-1998, and a facility survey that measured quality available from outpatient providers.Study design-Multivariate regressions are used to explain the quality of care received. Explanatory variables are high facility quality, maternal education, household we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The five areas addressed themes of early psychosis care and healthcare innovation and research including (Table ) Early psychosis treatment principles and practice Research priorities for early psychosis care and treatment Evidence‐based delivery methods for training and educating the workforce Implementation science and translating evidence into practice Improving patient care through innovation …”
Section: Methodsmentioning
confidence: 99%
“…The five areas addressed themes of early psychosis care and healthcare innovation and research including (Table ) Early psychosis treatment principles and practice Research priorities for early psychosis care and treatment Evidence‐based delivery methods for training and educating the workforce Implementation science and translating evidence into practice Improving patient care through innovation …”
Section: Methodsmentioning
confidence: 99%
“…To create our theoretical model, we reviewed previous studies [14][15][16][17], government reports [18][19][20][21][22], and other literatures [16,[23][24][25][26][27][28][29]. We selected the variables that have most commonly been shown to impact life expectancy, especially in Indonesia.…”
Section: Structural Equation Modelingmentioning
confidence: 99%
“…Socioeconomic and demographic factors also influence life expectancy [2,[14][15][16][17][23][24][25][26][27][28][29][30][31]. Declining of income inequality contributes to increasing life expectancy in Indonesia [30].…”
Section: Structural Equation Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Educated pregnant women are more likely to use antenatal care than the uneducated ones [9,12,13]. Barber and Gertler [14] have suggested that the least educated women groups in outer Java and Bali regions are the least likely to seek antenatal care and underutilising of antenatal care services has increased significantly among mothers with low levels of education. Those mothers with low educational attainment are likely to take less than four antenatal care visits as recommended [9].…”
Section: Maternal Education/lack Of Knowledge Of Antenatal Carementioning
confidence: 99%